Anti-aminoacyl-tRNA synthetase-interacting multifunctional protein-1 antibody improves airway inflammation in mice with house dust mite induced asthma - Kim, Sung Ryeol; Um, Yun Jung; Chung, Sook In; Jeong, Kyoung Yong; Park, Hye Jung; Park, Kyung Hee; Park, Jung Won; Park, Sang Gyu; Lee, Jae Hyun (World Allergy Organization Journal, 2024)
Background: Several biologics have been developed and used to treat severe asthma. However, commercialized biologics have limitations in treating T2-low asthma because their main target is the T2 inflammation marker. Therefore, there is an unmet need for treating T2-low severe asthma. Aminoacyl-tRNA synthetase-interacting multifunctional protein 1 (AIMP1) is an auxiliary protein in the mammalian multi-aminoacyl-tRNA synthetase complex. AIMP1 also acts as a cytokine and induces the secretion of proinflammatory cytokines. Since anti-AIMP1 has been shown to reduce interleukin (IL)-6, tumor necrosis factor-α, and IL-17A levels in a mouse model, it could be effective in the treatment of T2-low severe asthma. Methods: Wild-type BALB/c mice were sensitized and challenged with intranasal inoculation of a crude HDM extract. Atliximab, a chimeric AIMP1 antibody, was administered once (20 μg, 40 μg, 100 μg) on Day 14. We evaluated airway hyperresponsiveness (AHR), performed cellular analyses of the bronchoalveolar lavage fluid (BALF), measured inflammatory cytokine levels, and examined peribronchial histological features. Results: Atliximab reduced AIMP1 levels in asthmatic mice in a dose-dependent manner. AHR and Inflammatory cells such as neutrophils and eosinophils in the BALF decreased in asthmatic mice treated with atliximab. The levels of IL-6, IL-13, and transforming growth factor-β (TGF-β) in the lung tissue decreased in asthmatic mice treated with a high dose of atliximab (100 μg). Atliximab also reduced goblet cell hyperplasia and peribronchial fibrosis. Conclusions: Atliximab improved asthmatic airway inflammation including neutrophilic inflammation in HDM-induced asthma mice. These data suggest that anti-AIMP1 plays an important role in the treatment of severe T2-low asthma.
Keywords: AIMP1; Asthma; Interleukin-13; Interleukin-6